Over Ten-year Follow-up Study on Post-operative Results after Hemiarthroplasty for Femoral Neck Fracture - SUZUKI, Kazuhiro (Japanese Journal of Rheumatism and Joint Surgery, 1995)
Post-operative results of more than ten years after hemiarthroplasty for femoral neck fracture were reviewed for 21 joints in 21 cases. Clinical results showed 18 cases (85.7%) rated “excellent” or “good” based on assessment criteria of the Japanese Orthopaedic Association, and the average score of 87.8 points was in the “well” grade. Radiological results, showed stem sinking of more than 3 mm in all cases of the Moore type prosthesis without cement, in half of the Moore type with cement, and in no cases which used the Bateman type. Progression of stem sinking, however, had ceased approximately 3 years post-operatively, and did not influence the final clinical results. Acetabular erosion caused by the metal head was observed in one case of the Bateman type, in which radiogram showed findings of osteolysis at the superior and medial aspect of the metal head 10 years post-operatively. Total hip replacement was performed. It is concluded from these studies that good results can be obtained in hemiarthroplasty for the displaced fracture of femoral neck fracture in the elderly even after a long period, provided the operation is done with precise technique.